Influence of antidysbiotic drugs on the liver of rats with experimental non-alcoholic steatohepatitis - Levitsky, A. P.; Vasjuk, V. L.; Levchenko, E. M. (Journal of Education, Health and Sport, 2017)
High-fat diets combined with the introduction of lincomycin causes the development of steatohepatitis. Introduction antidysbiotic drugs (pro- and prebiotics) has a therapeutic effect.